Influence of remnant size on the geomechanical situation and safety in the mining field based on numerical modeling - Adach-Pawelus, Karolina; Pawelus, Daniel (Wroclaw University of Technology, 2025)
Great problem associated with the Polish underground mining is doing the mining operations at an increasing depth in difficult geological and mining conditions, among others, in the area of remnant impact. The problem with remnants and its effect on the rock mass behavior is an important issue in the Polish underground hard coal mines and copper mines. The main goal of the paper is to investigate how the different sizes of remnants affect the geomechanical situation in the mining field. Numerical simula-tions were conducted for the case study of a mining field with a room and pillar mining system, where undisturbed remnants 10, 20, 40, 60, 100, and 200 m in width, were left behind. Results of numerical analysis demonstrate that the size of remnant has a great influence on the stress distribution and rock mass stability in the mining field. As the width of the remnant decreases, the values of vertical stress σy both inside the remnants and in its surroundings increase and reach very high values for narrow remnants. In contrast to the vertical stress y, the strength factor Sf decreases as the width of the remnant decreases. Simulations show also that leaving a large remnant in the form of a stabilizing pillar, improves the stabil-ity of the roof in the mining field but for remnants with high widths an unstable zone might be formed in the roof layers above the edge of the remnant at the goaf side which may cause sudden fracturing and collapse of rigid roof layers on the edge of the remnant. The results achieve in this paper can be utilized to enhance the safety and efficiency of underground mining.
Mining Science, Vol. 32, 2025, s. 47-63
Keywords: mining; geology; geo-engineering